Using technology to assist creative arts activities in dementia care. (20th December 2022) - Christensen, Justin; MacRitchie, Jennifer; Floridou, Georgia; Timmers, Renee; De Witte, Luc
Abstract: Background: Alongside a growing use of creative arts within community and residential settings to support the health and wellbeing of older adults living with dementia, is an increasing availability of technology, although development for this context has up till now been limited. To examine how technology might be used to meet the leisure, health, and wellbeing needs of people living with dementia, we conducted a scoping review to assess the current state of development of creative assistive technologies across various art‐forms. Method: Our research questions asked i) what are the arts‐based activities being delivered through technology for older adults living with dementia or mild cognitive impairment, and ii) what are the characteristics of technologies being used to enhance these arts‐based activities? A comprehensive search was conducted using PubMed, PsychINFO, Web of Science, Scopus and ACM Digital Library databases. Two raters independently screened titles and abstracts, rating whether articles fit our inclusion criteria. A total of 3762 records were retrieved, of which 51 articles were included after full‐text screening. Result: Music (29), visual art (7), storytelling (6) and film‐making (2) were delivered through technology to older adults living with dementia. Other activities included dance (1), interactive light and sound (1), and incorporating arts activities into multi‐sensory objects (3). Two applications specifically allowed a choice between multiple creative arts (2). Single papers focused on Technologies were mainly custom‐made devices rather than applications using everyday devices such as smartphones or computers. Devices were often oriented towards individual use, supported by carers rather than groups of individuals at once, with fewer flexible in use alternate between solo/group. Outcomes measured were predominantly in terms of validating feasibility of the device and/or arts activity reported. Conclusion: Current research concerning technology‐assisted creative arts activities for people living with dementia mainly demonstrates feasibility of new devices, indicating that the field in general is predominantly in the prototyping stage. Future research should consider device development past prototyping, and consider comparing devices across different art‐forms i.e, applications having a varied range of artforms which allow for individual needs and interests to be accommodated.